Other voices: Native literature and issues of speech - Slater, Dennis (L'Uomo società tradizione sviluppo, 2019)
The article deals with the multi-faceted issue of native literature and the many questions it currently stirs about the correctness of non-native writings on native subjects, of native writings on non-native topics and so on. The range of opinions is very ample and includes different - sometimes opposite positions. Throughout the voices of a few Natives, the A. points to the issue that seems to arise as the main topicality from the debate, that is the necessity of a thorough research and knowledge as a basis for writing <<beyond one’s gender>> in order to avoid the risk of perpetuating false stereotypes. L’articolo tratta del complesso - attuale - problema della letteratura nativa e delle diverse domande intorno allo possibilita per autori nativi di scrivere correttamente su temi non nativi, per autori non nativi di farlo sulle culture native e cosi via. Lo spettro delle risposte e vasto e include opinioni differenti, talvolta contrastanti. Attraverso i pareri di alcuni Nativi l’A. riconduce i termini del problema alla questione dominante che sembra emergere dal dibattito, quella cioé della necessità, per chiunque scriva <<al di fuori del proprio campo>>, di basarsi su approfondite ricerche e conoscenze onde evitare il rischio di avvalorare fuorvianti stereotipi letterari.